2022
DOI: 10.1021/acs.inorgchem.2c02672
|View full text |Cite
|
Sign up to set email alerts
|

Amine-Functionalized Carbon Bowl-Supported Pd-La(OH)3 for Formic Acid Dehydrogenation

Abstract: Formic acid (HCOOH, FA) is emerging as an appealing carrier for hydrogen storage owing to its renewability, a high volumetric capacity of 53 g H 2 / L, and convenient storage/transportation as a liquid. It is highly desired but still a challenge to search highly efficient catalysts to realize hydrogen evolution from FA. Here, monodispersed and ultrasmall Pd−La(OH) 3 nanoparticles (NPs) anchored on amine-functionalized N-doped porous carbon bowl (N-PCB-NH 2 ) substrates have been fabricated through a facile wet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…It can be concluded that the introduction of Cr­(OH) 3 can reduce the strong acid sites and increase the concentration of basic sites in the catalyst. As a higher density of surface basic sites can play a role in regulating the micro-pH value and has been shown to promote the O–H bond dissociation of FA molecules, , Pd–Cr­(OH) 3 /NH 2 -rGO catalyst is expected to exhibit excellent catalytic activity toward FAD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be concluded that the introduction of Cr­(OH) 3 can reduce the strong acid sites and increase the concentration of basic sites in the catalyst. As a higher density of surface basic sites can play a role in regulating the micro-pH value and has been shown to promote the O–H bond dissociation of FA molecules, , Pd–Cr­(OH) 3 /NH 2 -rGO catalyst is expected to exhibit excellent catalytic activity toward FAD.…”
Section: Resultsmentioning
confidence: 99%
“…Heterogeneous catalysts are more stable and more easily achieve catalyst separation and recovery than do homogeneous catalysts. , It has been shown that Pd is more resistant to CO than other metals and is the essential active metal for FAD, and the alloys of Pd with other noble metals such as Au, Ag, and Ir have excellent activity for FAD. However, the practical applications of precious metal elementals can be limited by their high cost and low reserves. An attractive strategy for saving costs and improving catalytic activity is to develop a durable and effective Pd catalyst modified with nonprecious metal. Attaching Pd to a transition metal can make them equal at the Fermi level, which is an effective way to modulate the electronic structure of the Pd active center and thus achieve enhanced synergistic catalysis during Pd-catalyzed processes . Recently, Cr, an earth-abundant and low-cost transition metal, has been utilized for forming uniformly distributed metal nanoparticles (NPs). Therefore, Cr species can be expected as a favorable accelerator of Pd catalyst to boost FAD.…”
Section: Introductionmentioning
confidence: 99%
“…Pd-based nanocatalysts are most attractive for practical hydrogen generation from FA decomposition due to their high catalytic activity and CO-free behavior at the low reaction temperature. 17,18…”
Section: Introductionmentioning
confidence: 99%
“…The enhanced catalytic performance of the bimetallic catalysts can be due to the electron-rich Pd active sites induced by the Pd−Ni alloying effect, as shown by the XPS studies. The electron-rich Pd surface favors the activation of the C−H bond h i b i t e d .of the Pd−formate intermediate to produce H 2 and CO 2 62,63. The activity of the physical mixture of Pd/KIT-6-NH 2 , Ni/ KIT-6-NH 2 , and WO x /KIT-6-NH 2 is much lower than that of PdNi-WO x /KIT-6-NH 2 under the same conditions (FigureS13, Supporting Information), confirming the synergistic alloying effect of Pd and Ni.…”
mentioning
confidence: 99%